Prima Krim sebagai Solusi Penyembuh Luka pada Penderita Diabetes Meli - Rahmad Dwi Ardhiansyah; Riefky Pradipta Baihaqie; Muhammad Nuriy Nuha Naufal; Muhamad Atabika Farma Nanda; Kurnia Rahmawati; Yuda Heru Fibrianto (Jurnal Sain Veteriner, 2019)
Number of patients with diabetes mellitus are very large, according to International Diabetes Federation (IDF) in 2013 reaches 382 billion people between the ages of 40-59 years. Diabetic has been characterized as a chronic wounds. The animal blood waste from a slaugther house is still untapped, containing PRP (Platelet Rich Plasma) that can accelerates heal of bone and soft tissue. PRP (Platelet Rich Plasma) was made from the cattle blood waste using centrifugation. The purpose of the study is to prove that the Prima cream can heal the wounds in diabetic patients. Animals used in this study is 20 Wistar rats. Induction of diabetes was using streptozootocin 65 mg/kg and nicotinamide 235 mg/kg. The animal were divided into 4 groups: non-diabetes given placebo (ND-), diabetes given placebo (DM-), diabetic rat given commercial drug were containing chloramphenicol base 20 mg + prednisolone 2.5 mg (DM+), and diabetes given cream PRP at 20% concentration (DM PRP). Parameters used to measure the rate of wound healing is wound size and histopathologic examination. The data were analyzed using Anova One Way at 95% significant rate. PRP DM group had a wound healing faster than ND- group, DM- and DM+. Based on histopathologic examination, such as epitelialization, basal membrane, fibroblasts, collagen tissue, and presence of inflammatory cells, the best curing reaction was showed in DM PRP. PRP 20% cream produces from cow blood waste can accelerate wound healing in diabetes mellitus.